Heat capacity of methane-krypton solid solutions. Conversion effect - Minchina, I. Ya.; Manzhelii, V. G.; Bagatskii, M. I.; Sklyar, O. V.; Mashchenko, D. A.; Pokhodenko, M. A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2001)
The heat capacity of Kr-nCH4 solid solutions with the concentrations n= 1; 5; 10% and of the solid solution Kr-1%CH4-0.2%O2 has been studied at 0.7-8 K. The contributions of Crot to the heat capacity of the solutions caused by the rotation of the CH4 molecules are estimated. The deviations of themeasured Crot from the values corresponding to the equilibrium distribution of the nuclear spin CH4modifications are dependent on the correlation between the characteristic times of conversion and of thecalorimetric experiment. The effects of temperature, O2 impurities, and CH4 clusters upon the conversion rate are studied. It is shown that the hybrid mechanism of conversion proposed by Berlinsky and Nijman,which takes into account both intramolecular and intermolecular interactions of the proton spins, is predominant.